Diseño de un sistema eficiente para accionamiento de máquinas hidráulicas de extracción de jugo de caña de azúcar. - Eras, Darwin Medardo (2004)
The present work is about the parameters of exploitation of hydraulic wheel used in the sugar cane mills, for the elaboration of not centrifuged sugar or scrape and distillation of liquor, using the hydraulic energy of artificial waterfall in small fluent. The methodology of calculation of hydraulic the wheel with superior feeding without head of water and different mechanical elements that conform the system (trees, joinings, cotters, gears, etc.) is realized, a system of recirculation of fluid by means of a hydraulic battering ram that allows to achieve a bigger use of the available water is also annexed. Based on the obtained results it is demonstrated that the Hydraulic Wheel constitutes an economic alternative in the energy helping to save and to preserve the environment.